Aeschylus' Oresteia. - Conacher, D. J. (University of Toronto Press, 1989)
The major part of Conacher's work is a detailed running commentary on, and dramatic analysis of, the three plays. It is supplemented in notes and appendixes by discussions of the philological problems relevant to the interpretation, and by a sampling of other scholaraly views on a number of controversial points.